Building Islamic Character in Students Through the One Day Boarding Program: Pembentukan Karakter Islami Siswa Melalui Program One Day Boarding - Fahyuni, Eni Fahriyatul; Wijayanto , Anang (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The current era presents significant moral challenges, highlighting the critical role of character education in preparing students for a valuable life in society. Specific background: This study investigates the